DEPENDENCY RELATIONSHIP OF EXERCISE AND MEDICATION ADHERENCE IN HYPERTENSIVE PATIENTS. (June 2022) - Fragoulis, Christos; Prentakis, Andreas G.; Kontogianni, Evangelia; Polyzos, Dimitrios; Leontsinis, Ioannis; Mantzouranis, Emmanouil; Kalos, Theodoros; Politis, Antonios; Tsioufis, Konstantinos
Abstract : Objective: Few studies have examined the relationship between exercise and adherence to antihypertensive medication, examining all possible factors contributing to blood pressure control. The purpose of our study was to access the possible dependence relationship among hypertensive patients visiting the Behavioral Cardiology Unit in a Tertiary Hospital. Design and method: The study population consisted of patients reporting to the Behavioral Cardiology Unit in a Tertiary Hospital during a period of 6 months in 2021. In terms of holistic approach, all patients underwent a thorough clinical in-depth interview, using the Morisky Medication Adherence Scale (MMAS8), the Frail Questionnaire Screening Tool (Frailty Score) and the Patient Health Questionnaire-4 (PHQ-4). All patients also provided full history of exercise (at least 150 minutes of physical activity or 75 minutes of intense activity per week), while completing the Duke Activity Status Index (DASI). Results: The population consisted of 42 hypertensive patients, 54.8% of them were females, with a mean age of all patients at 55.8 ± 15.2 years. Body Mass Index was averaging at 27.6 kg/m2. Salt consumption above the daily suggested amount (>5gr/day) was reported by 60% of patients, binge drinking by 43% of them, while 43% had a history of active smoking. High adherence was reported by 17 patients (46%), medium adherence by 14 (37.8%) and low adherence by 6 (16.2%). Results indicate a relationship between exercise and adherence to medication. More specifically, Chi-Square test showed statistical significance between exercise and medium medication adherence in MMAS8 (MMAS8: 6–7, p = 0.033). Moreover, statistical analysis showed significant relationship between exercise, frailty and PHQ-4 score. Particularly, patients with absence of exercise showed higher level of PHQ-4 score (F = 7.07, p = 0.011). Conclusions: Our study highlights the possible dependency relationship of exercise and adherence to medication. Results indicate that patients with good adherence to medication have better behavioral activation. There is need for further research in this domain, to confirm the findings.